IMPACTS OF EXTERNAL FINANCING ON THE RISK LEVEL OF VIET NAM NATURAL GAS AND OIL INDUSTRY DURING AND AFTER THE GLOBAL CRISIS 2007-2009 - Ngoc Huy, Dinh Tran (International Journal of Research -GRANTHAALAYAH, 2015)
This paper estimates the impacts of external financing on market risk for the listed firms in the Viet nam natural gas and oil industry, esp. after the financial crisis 2007-2009. First, by using quantitative and analytical methods to estimate asset and equity beta of total 15 listed companies in Viet Nam natural gas and oil industry with a proper traditional model, we found out that the beta values, in general, for many institutions are acceptable. Second, under 3 different scenarios of changing leverage (in 2011 financial reports, 30% up and 20% down), we recognized that the risk level, measured by equity and asset beta mean, decreases (0,231) when leverage increases to 30% and vice versa. Third, by changing leverage in 3 scenarios, we recognized the dispersion of risk level decreases (measured by equity beta var) if the leverage increases to 30%. Finally, this paper provides some outcomes that could provide companies and government more evidence in establishing their policies in governance.